Suami Sebagai Kepala Keluarga (Efesus 5:22-33) Dalam Mencegah Kekerasan Dalam Rumah Tangga - Simbolon, Lena Christina (Prodi Teologi IAKN Tarutung, 2024)
Domestic violence often occurs in family life, including in Christian families. The understanding of the husband as the head of the family is often interpreted as if the husband is a head or boss who is served by his servants. The wife is considered to be someone who is lower in position than her husband. Paul in Ephesians 5:22-33 emphasizes the relationship between the husband as the head of the family towards his wife like Christ as the head of the congregation. This is the relationship between husband and wife that God desires in the household life of believers, namely loving each other. This paper uses a qualitative writing method, namely the library research approach. The library research method will be carried out through the collection of library data such as books, journals and internet sources.